2021
DOI: 10.1093/brain/awab342
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparity is associated with faster retinal neurodegeneration in multiple sclerosis

Abstract: Disease course in multiple sclerosis is notably heterogenous, and few prognostic indicators have been consistently associated with multiple sclerosis severity. In the general population, socioeconomic disparity is associated with multimorbidity and may contribute to worse disease outcomes in multiple sclerosis. Herein, we assessed whether indicators of socioeconomic status (SES) are associated with disease progression in people with multiple sclerosis using highly sensitive imaging tools like optical coherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
1
14
0
2
Order By: Relevance
“…Most previous studies on SES in the context of MS have focused on susceptibility rather than severity, and results have been conflicting . A few studies looking at severity have demonstrated correlation to postcode-based socioeconomic indices, similar to our findings. Only 1 of these studies accounted for DMT exposure, and all measured SES at or after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies on SES in the context of MS have focused on susceptibility rather than severity, and results have been conflicting . A few studies looking at severity have demonstrated correlation to postcode-based socioeconomic indices, similar to our findings. Only 1 of these studies accounted for DMT exposure, and all measured SES at or after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The GCIPL is a better biomarker of atrophy than peripapillary nerve fiber layer thickness because its loss can be detected much earlier. 17,31 Both the reviewers of MRI and OCTs were blinded to the clinical data.…”
Section: Methodsmentioning
confidence: 99%
“…15 This observation may be unique to particular parts of the CNS and does not necessarily apply to all CNS structures. Optical coherence tomography (OCT) imaging is a tool used to longitudinally quantify retinal neurodegeneration in MS, [16][17][18] and its measures have been shown to correlate with disability, 19,20 brain neurodegeneration, 21 and cortical lesions. 22 The brain cortex and retina have different cytoarchitectures, with a greater proportion of tissue volume in the retina coming from neurons/axons and greater heterogeneity of neuronal subtypes as well as the presence of oligodendrocytes in the cortex (Figure 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Available data regarding the effect of socioeconomic status on MS disability outcomes indicate a relationship between greater deprivation at disease onset and greater disability even in countries with a universal health-care system, including a higher risk of reaching EDSS scores of 4.0 and 6.0 in Cox proportional hazards models 46,48 , faster retinal neurodegeneration 49 and onset of secondary progression 46 . Evidence also indicates that higher socioeconomic status in people with MS is associated with a lower burden of psychiatric symptoms and a higher likelihood of symptom recovery following mental health treatment 50,51 .…”
Section: Race and Ethnicitymentioning
confidence: 99%